Comparison of the efficacy of amoxicillin-clavulanic acid with metronidazole to azithromycin with metronidazole after surgical removal of impacted lower third molar to prevent infection - Sayd, Shermil (J Korean Assoc Oral Maxillofac Surg, 2018)
OBJECTIVES: The goal of the study was to investigate the clinical effects of amoxicillin-clavulanic acid (500+125 mg) with metronidazole 400 mg administered three times daily (Group I) versus azithromycin 500 mg administered once daily and with metronidazole 400 mg three times daily (Group II) for the prevention of postoperative infection following mandibular third molar surgical removal. MATERIALS AND METHODS: The study design was a single-center prospective study. Patients who reported to the Department of Oral and Maxillofacial Surgery between February 2015 and January 2017 for removal of mandibular third molar were screened, and 108 patients were chosen. One surgeon carried out all procedures. Patients were prescribed antibiotics until the two groups contained a similar number of cases. RESULTS: Our data showed that Group II had fewer incidences of surgical site infection, but with no statistical significance. CONCLUSION: Although both treatments are used routinely after removal of the mandibular third molar, neither is significantly better than the other.